Emotional Intelligence of Teenagers Addicted to Online Games: Kecerdasan Emosional Remaja yang Kecanduan Permainan Online - Suryawan, Ana Fatimah; HAZIM (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Online games have become a dominant form of entertainment for adolescents in Indonesia’s digital era. Specific background: While these games offer enjoyment, excessive use can lead to addiction and negatively affect emotional intelligence, which is crucial for adolescents’ academic and social development. Knowledge gap: Previous studies have explored the psychological and social effects of gaming, but limited research has focused on how online game addiction shapes emotional intelligence among Indonesian high school students. Aim: This study investigates the emotional intelligence profile of adolescents addicted to online games at Muhammadiyah X Taman High School. Results: Using a qualitative phenomenological method with two subjects aged 15–18 years, data collected through in-depth interviews were analyzed using Miles and Huberman’s framework. Findings reveal that both subjects demonstrate low levels of emotional intelligence, reflected in difficulties with self-awareness, emotional regulation, motivation, empathy, and social skills, which in turn disrupt their academic responsibilities and social interactions. Novelty: This study provides nuanced evidence of how intensive online gaming alters emotional and behavioral patterns in adolescence. Implications: The results highlight the urgent need for targeted educational and parental interventions to strengthen adolescents’ emotional regulation and promote healthier engagement with digital media. Highlights: Teenagers addicted to online games show low emotional intelligence. Key aspects affected include self-awareness, empathy, and social skills. Intensive gaming disrupts academic tasks and social interactions. Keywords: Emotional Intelligence, Online Game Addiction, Adolescents, Behavioral Patterns, Qualitative Study